The Edmonton Classification System for Cancer Pain: a tool with potential for an evolving role in cancer pain assessment and management. Issue 2 (4th May 2018) - Lawlor, Peter G; Lawlor, Niamh A; Reis-Pina, Paulo
ABSTRACT: Introduction : Undertreatment of cancer pain is associated with inadequate assessment and inconsistent or non-standardized classification, resulting in failure to both appreciate its multidimensional nature and appropriately target therapeutic interventions. This review examines the classification of cancer pain with a focus on the progressive development of the Edmonton Classification System for Cancer Pain (ECS-CP); the appropriateness of its constituent features, associated outcomes and its potential future development in cancer pain classification. Areas covered : A Medline search from 1989 to November 2017, using combined terms 'cancer' or 'oncology', 'Edmonton', 'pain' or 'analgesia', and 'staging' or 'classification', identified 280 records. A total of 20 studies with empirical data relating to validation studies of the ECS-CP or evaluation of either its constituent or proposed domains were selected for inclusion in the core review. Expert commentary : The ECS-CP is a tool in evolution and a valid template for further cancer pain classification development. The assessment of ECS-CP domains requires a standardized approach. The domain ratings can inform the therapeutic strategy, and are associated with pain management outcomes, particularly stable pain control. The ECS-CP enables standardized reporting, based on patients' pain and related characteristics, and thus may improve the validity of comparisons across research study samples.